Chaos synchronization for hyperchaotic lorenz-type system via fuzzy-based sliding-mode observer - Plata-Ante, Corina (My University, 2020)
Hyperchaotic systems have applications in multiple areas of science and engineering. The study and development of these type of systems helps to solve diverse problems related to encryption and decryption of information. In order to solve the chaos synchronization problem for a hyperchaotic Lorenz-type system, we propose an observer based synchronization under a master-slave configuration. The proposed methodology consists of designing a sliding-mode observer (SMO) for the hyperchaotic system. In contrast, this type of methodology exhibits high-frequency oscillations, commonly known as chattering. To solve this problem, a fuzzy-based SMO system was designed. Numerical simulations illustrate the effectiveness of the synchronization between the hyperchaotic system obtained and the proposed observer
Mathematical and computational applications
Keywords: Hyperchaotic system; Fuzzy-based; Sliding-mode; Campus Tijuana